Phytoplankton blooming mechanisms over the East China Sea during post-El Niño summers - D.-G. Lee; D.-G. Lee; J.-H. Oh; J. Kam; J.-S. Kug; J.-S. Kug (Biogeosciences, 2025)
During post-El Niño summers, the East China Sea (ECS) experiences anomalous phytoplankton blooming, but the understanding of associated generating mechanisms remains limited. Here, we analyzed observational (25 years) and long-term simulation data (1000 years) to investigate the underlying mechanisms for the anomalous phytoplankton blooming in the ECS. Results highlight three mechanisms associated with enhanced phytoplankton blooming in the ECS during post-El Niño summers: inland runoff, nutrient inputs from the Taiwan Strait (TS), and oceanic subsurface upwelling-driven blooming mechanisms. Firstly, increased river discharge from the Yangtze River (YR) induces phytoplankton blooms. Secondly, enhanced nutrient inputs through the TS promote phytoplankton growth. Additionally, wind-driven Ekman upwelling in the ECS provides nutrients for phytoplankton growth from the subsurface to the surface water layer. These three mechanisms are all linked to the western North Pacific anticyclone (WNPAC), suggesting the WNPAC can be a key precursor to predict ECS blooming. Climate model simulations support these complex mechanisms, and thus our results suggest that all mechanisms can contribute to the phytoplankton bloom concurrently.